2019
DOI: 10.37358/mp.19.2.5194
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Polymeric Magnetic Encapsulated Nanoparticles on the Adhesive Layer for Composite Materials Used for Class I Dental Fillings

Abstract: The main properties of dental adhesives should be good marginal adaptation, high retention strength and the possibility of not negatively influencing clinical sustainability. Dental adhesives are continuously improving to increase their retention to dental structures by increasing penetration in these structures, as it was shownin the in-vitro tests requiring imaging and qualitative analysis to allow the evaluation of experimental samples as well as the development of new materials. The main objective of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…To our knowledge, we have proposed using MPs for the first time in a series of preliminary studies [ 36 , 37 , 38 ] with the scope of obtaining a tighter connection between the composite material and the dental surface [ 39 , 40 ] and therefore a smaller thickness of the dental adhesive compared with a conventional treatment. To demonstrate the effect of the MPs, dental adhesives with or without MPs have been utilized in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, we have proposed using MPs for the first time in a series of preliminary studies [ 36 , 37 , 38 ] with the scope of obtaining a tighter connection between the composite material and the dental surface [ 39 , 40 ] and therefore a smaller thickness of the dental adhesive compared with a conventional treatment. To demonstrate the effect of the MPs, dental adhesives with or without MPs have been utilized in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], including MPs are largely used in medicine [ 31 , 32 , 33 , 34 , 35 ]. To our knowledge, we proposed using MPs for the first time in a series of preliminary studies [ 36 , 37 , 38 ] with the scope of obtaining a tighter connection between the composite material and the dental surface [ 39 , 40 ], compared with a conventional treatment. To demonstrate the effect of the MPs, dental adhesives with or without MPs are used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…In order to be able to use the as-prepared dental magnetic composites in dental restorative applications under an external magnetic field, the minimum requirement is that this type of material has relatively good magnetic properties so that it interacts properly with the field. Magnetic measurements support the idea of applying the as-prepared dental magnetic material on the tooth surface under an external magnetic field, a method with a major impact on reducing the occurrence of dental caries under filling materials as well as on reducing microfractures [ 38 , 46 ]. In Figure 2 , the hysteresis loops at room temperature of the MNPs Fe 3 O 4 -SiO 2 and Ca(OH) 2 are presented.…”
Section: Discussionmentioning
confidence: 99%
“…Another innovative idea of this article is that, based on the presence of the magnetic phase in composition, application on the tooth surface will be achieved under an external magnetic field, which compared to conventional application methods has a major impact on reducing and homogenizing the thickness of the adhesive layer and reducing the occurrence of dental caries under filling materials as well as on reducing microfractures. A preliminary study that supports this idea is presented in our previous research, in which it is shown that the incorporation of magnetic nanoparticles into dental adhesives can reduce the thickness of the adhesive layer by 30% after applying a magnetic field on the tooth surface for 2 min and by 86.5% after applying the same magnetic field for 5 min, compared to the application of dental adhesives by conventional techniques [ 46 ]. In addition, the dental composite material is prepared by a combined preparation method, which involves several simple, cost-effective and environmentally friendly reaction steps, thus giving the final material a relatively low-cost price.…”
Section: Introductionmentioning
confidence: 90%